World cinema at Soviet festivals: cultural diplomacy and personal ties. Issue 2 (3rd May 2020) - Razlogova, Elena
ABSTRACT: This article traces informal world cinema networks at Soviet film festivals. It argues that the cultural diplomacy approach, where state objectives determine the value of cultural exchange, fails to account for the full range of connections made at Soviet film festivals during the Cold War. Personal ties have been crucial to the development of film festivals and the cinematic movements they engendered. The Soviet state aimed to position Soviet cinema as a better alternative to decadent European and commercial Hollywood cinemas, and as a model for film cultures in socialist Eastern Europe and decolonization-era Asia, Africa, and Latin America. This article first demonstrates how the Moscow International Film Festival (1959-present) and the Tashkent Festival of Asian, African, and Latin American Cinema (1968–1988; Latin America included from 1976) constructed a more inclusive map of world cinema than major European film festivals at Cannes, Venice, and Berlin. It then shows how African, Cuban, and Vietnamese delegations forged informal alliances around the emergent Third Cinema (militant Third World cinema) movement at the 1967 Moscow festival. Strong unofficial connections formed by international festival guests transcended and contradicted the aims of Soviet cultural diplomacy.